Evaluating Efficacy of Vedolizumab, Ustekinumab, and Golimumab in the Management of Inflammatory Bowel Disease and the Combined Role of Nutritional Therapy with Biologics: A Review - Shahed Kamal; Karan Varshney; Danielle Josefa F. Uayan; Fides Myles C. Caliwag (Biologics, 2024)
Inflammatory bowel disease (IBD), which encompasses both ulcerative colitis (UC) and Crohn’s disease (CD), is a major health burden worldwide. There are increasing concerns surrounding the impacts of this disease due to significant rises in the prevalence rates of IBD across the world. In consideration of the complexities of managing IBD along with this marked rise in prevalence and incidence, developing new forms of treatment for this condition has become a major priority. In recent years, a potential new form of treatment for IBD has emerged in the form of biologic therapies. While there is a high level of optimism due to the development of these therapies, there is also a clear need to evaluate their effectiveness, and their overall safety profiles. For this review, we have evaluated three specific biologics used for the treatment IBD. More precisely, the focus of this review is to analyze and critically appraise the literature for vedolizumab, ustekinumab, and golimumab, and determine their roles in the management of UC and CD, respectively. After doing so, we have also briefly synthesized important new findings regarding the role of dietary and nutritional approaches. In doing so, we have aimed to contextualize the findings regarding biologics, and, in order to evaluate potential new treatment approaches for the future to augment biologic therapies, we have discussed the potential for combined approaches that incorporate the usage of both biologics and nutritional interventions for patients.